An expanded view of psychological aspects in head pain: the biopsychosocial model - Andrasik, Frank; Flor, Herta; Turk, Dennis C. (Neurological sciences, 2005)
Traditionally, headache has been viewed from a limited perspective, both medically and psychologically. The authors propose that a more expanded view of headache that considers each perspective as important, as embodied in the biopsychosocial model, will greatly enhance understanding and be more useful in treatment planning. This model views pain as emanating from a complex interaction of biological, psychological and social variables. This paper describes the key behavioural, affective and cognitive influences and provides pertinent supporting examples from the literature.
Gesehen am 10.11.2020